THE FACTORS THAT INFLUENCE DEMAND PERSONAL CONSUMERS PLEASE ( MYSTACOLEUCUS PADANGENSIS) IN OMBILIN MARKET SINGKARAK SUBDISTRICT DATAR WEST SUMATERA PROVINCE - Putri, Dila Kartika; Bathara, Lamun; Hamid, Hamdi Hamid (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT            This research was conducted in April 2017 located in Ombilin Singkarak Mareket, Rambatan District, Tanah datar Regency, West Sumatera Province. This study is appropriate for request of Bilih fish and to know the factors – factors that affect the demand of fish Bilih in Ombilin Market. The method used in this study is a survey method, where the determination of respondents to traders and consumers using the method of accidental sampling.            The result of the research shows that the demand of Bilih fish when the Bilih fish production is decreasing and the demand is increasing so the Bilih fish price is increasing due to the decreasing production. With the transition state of fish consumers. Factors – factors that effect demand Bilih fish in Ombilin Singkarak market that is equal to 99,6 %. Of 99,6 % factors that greatly affect the demand of Bilih fish in Ombilin Singkarak Market is the variable price of income (X4) of 0,000 namely Turiak fish (X3) of 0.142, Selera (D1) of 0.431 and time (D2) of 0.204 The effectiveness of Bilih fish demand in Ombilin Market is 99,6 % while the remaining 0,4 % ( 100% - 0,6%) not owned by the linear regression model.Keywords :Factors Affecting Consumer Demand, Bilih Fish, Ombilin Market